2021
DOI: 10.1002/rcm.9158
|View full text |Cite
|
Sign up to set email alerts
|

Identification of C‐glycosyl flavones and O‐glycosyl flavones in five Dendrobium species by high‐performance liquid chromatography coupled with electrospray ionization multi‐stage tandem MS

Abstract: Flavones are widely used in traditional Chinese medicine (TCM) and are the pharmacologically active ingredients of many medicinal plants, such as Dendrobium. With the increasing demand for medicinal Dendrobium, the identification of characteristic flavones that can serve as chemical markers for quality control is critical step for quality assurance and safety in the TCM industry. Methods: High-performance liquid chromatography coupled with electrospray ionization multi-stage tandem mass spectrometry (HPLC/ESI-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“…According to our previous research, most of the flavonoid glycosides in Dendrobium are C ‐glycosylated flavones, and their acylated derivatives in some Dendrobium varieties also have certain characteristics. The flavonoid aglycones mainly included apigenin [Ag = 270], luteolin [Ag = 286], and chrysoeriol [Ag = 300] 10–15 . In this study, C ‐glycosylated flavones were also found in D. hancockii , but the main constituent was O ‐glycosylated flavones, among which 5,7‐dihydroxyflavone [Ag = 254] has rarely been reported in other species.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…According to our previous research, most of the flavonoid glycosides in Dendrobium are C ‐glycosylated flavones, and their acylated derivatives in some Dendrobium varieties also have certain characteristics. The flavonoid aglycones mainly included apigenin [Ag = 270], luteolin [Ag = 286], and chrysoeriol [Ag = 300] 10–15 . In this study, C ‐glycosylated flavones were also found in D. hancockii , but the main constituent was O ‐glycosylated flavones, among which 5,7‐dihydroxyflavone [Ag = 254] has rarely been reported in other species.…”
Section: Resultsmentioning
confidence: 69%
“…For example, C ‐glycosyl flavones have been shown to lose 120 and 90 Da, corresponding to hexose substituents; 90 and 60 Da corresponding to pentose substituents; and 104 and 74 Da, corresponding to methyl pentose substituents 17 . Furthermore, the intensity of − 0,2 X is greater than that of − 0,3 X. Glucose, arabinose, xylose, and rhamnose moieties are the most common glycosyls in the flavonoids of Dendrobium 10–15 . The method of determining the substituted forms of C ‐glycosylated flavones allows the identification of the flavonoid glycosides as 6/8 mono‐ C ‐glycosyl flavones of the corresponding aglycone, when characteristic ion peaks of [Ag + 41] − , [Ag + 71] − , [Ag + 41–18] − , and [Ag + 71–18] − fragments appear in the mass spectrum, or as 6,8‐di‐ C ‐glycosyl flavones of the corresponding aglycone, when characteristic fragment ion peaks of [Ag + 83] − , [Ag + 113] − , [Ag + 83–18] − , and [Ag + 113–18] − are observed 29,30 (Ag: aglycone molecular mass).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…They serve as antioxidants, UV-protectants and play a pivotal role as coloring components of flowering plants [ 100 ]. MS/MS analysis can provide structural information about flavonoids including the structure of aglycones, glycosylation patterns and the presence of other substituents such as 3-hydroxy-3-methylglutaryl and other acyl residues [ 101 ]. According to previous studies of P. sarmentosum , the major identified flavonoid aglycone was apigenin (aglycon m/z 271) [ 102 ].…”
Section: Resultsmentioning
confidence: 99%